Ecophysiological response of Astronium fraxinifolium (Anacardiaceae) in degraded and non-degraded brazilian Cerrado - Leite, Marilaine Cristina Marques [UNESP] (2021)
Plants native from Cerrado generally have peculiar characteristics that allow tolerating water and nutritional stress. Astronium fraxinifolium is a Anacardiaceae tree of from Brazilian Cerrado. The aim of this research was to characterize A. fraxinifolium leaves morphophysiologically, in order to recognize characteristics related to acclimatization of the species in different soil conditions. Two populations of A. fraxinifolium were sampled in different study areas, A1 (Degraded Soil) and A2 (“Undegraded Soil”). Nitrogen compounds, total carbohydrates, chlorophyll, nutritional content, stomatal density and gas exchanges were quantified, comparing the areas. A high number of stomata was observed on the abaxial surface of A. fraxinifolium leaves, with a higher density occurring in A1 individuals. The values ​​of chlorophyll and boron content were significantly higher in A2 plants. It’s possible that the lowest concentration of boron in A1 plants is related to chlorophyll production. Regardinf the other analysis, there weren’t significant differences between the areas. The results show that this species undergoes changes in production of chlorophyll, but liquid photosynthesis isn’t impaired, considering the low chlorophyll content in A1 being compensated by the higher stomatal density. Thus, these changes may be the result of acclimating this species to different environmental conditions to which it’s exposed.